“Síntese e caracterização de perovskitas sem e com dopagem de Nb2O5” - Rigoni, João Francisco (2014)
The current technological development in the communication, has carrieb, data processing, integration of devices and entertainment, is only possible due to the advances integrated and continuos of the research on new materials to be applied in the technological industry,lighter, cheaper with better incomes. In the work it was become fulfilled synthesis and of the Titanate od calcium and has covered – pure CCTO and its doped version with different ratios of Nb+5 , by means of the method of reaction for solid state. This materials has shown interesting and pertinent physical properties to the current industry technological, as material mainly dielectric. The characterization of material obtained was made through the techniques of diffraction of X-rays (XRD), structural analysis for the Method of Rietveld, morphological and compositional characterization using scanning electron microscopy (SEM), dispersive spectroscopy X-ray (EDX), in addition to the characterization by Raman spectroscopy, and determination of the “band gap” by diffuse reflectance. The gotten, pure and doped samples had been identified as being the material of interest, proven through the described instrumental techniques previously. The gotten Values of “band gap” better present small variation, being able to be studied with use of others techniques.